A record of research directed towards enhancement of the safety of clinical anaesthesia - Harrison, Gaisford Gerald (Department of Anaesthesia, 2017)
Clinical Anaesthesia is an indispensable adjunct to the surgical treatment of disease. It directly affects the lives of a great number of people since every year no fewer than one in every twenty-five persons in the population is required to undergo a procedure which necessitates it. Of itself non-therapeutic, clinical anaesthesia must, above all else. be safe for the patient. Any adverse outcome to clinical anaesthesia and factors relevant to its administration results, at best, in postoperative morbidity for the patient and, at worst, his demise. Identification and examination of the factors and circumstances which have a material influence on the safety of anaesthesia for the patient, provided the motivation for and is the central theme of this collection of research publications which was submitted to the University of Cape Town in fulfilment of the requirements for the award of the Degree of Doctor of Science (Medicine). The publications submitted report the results of forty years of endeavour. In terms of their subject matter, these publications may be broadly grouped into the following five fields of interest: - 1) The Epidemiology of Death Attributable to Anaesthesia. 2) Pharmacogenetic States of concern to the Anaesthetist - a) The Malignant Hyperthermia Myopathy. b) The Acute Porphyrias. 3) The Effects of Anaesthetics on the Liver - Studies of Hepatic Drug Metabolism of relevance to post-Halothane Hepatitis and the hepatotoxicity of anaesthetic agents. b) The treatment of Fulminant Liver Failure. 4) Heat Homeostasis during Anaesthesia - a) Inadvertent Hypothermia during anaesthesia. b) Induced Hypothermia during anaesthesia. 5) Miscellaneous. Within these fields of interest, papers have been grouped in terms of related aspects of the main topic they cover. Editorial comment is included where appropriate. The nature and scope of many of the above investigations was such as to require, for their satisfactory conclusion, collaborative interdisciplinary research combining the endeavours of other clinicians and paramedical scientists. Appropriate recognition of such collaboration has resulted in the multiple authorship registered for many of the publications in this collection.